Gouvernance de la nouvelle Province de la Tshopo en RDC. Envol ou décollage raté ? - ZAMBA, Par Casimir NDEKE; TANYOBE, Emmanuel TAMIDRIBE (IJRDO-Journal of Applied Science, 2018)
Of narrative manner in leaning on the methodological approach of the immediate history, this article asks itself on the governance of the new Province of Tshopo, through its first actors, to know if this governance permitted the takeoff or no of this province. If the article examined the games of actors of the executive and the legislative provincial, it didn’t lack to lean over on the reaction of the population facing these games. It proved to be that the provincial assembly and the provincial Government filled their missions with many difficulties. The provincial government was far of requirements of populations. All those represented in its program were enumerative that’s means a chimerical reality to the population of the Province of Tshopo; save some actions of sprinklage, such asphaltage of three kilometers and the investment of some solar panels for the streetlight in city of Kisangani. And the provincial assembly didn’t make better.